Trade agreements as self-protection - Jennifer Pédussel Wu (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
Risks that are associated with an uncertain trading world have been dealt with using two different techniques in the literature: defensive, or insurance approaches, and preventive, or self-protection approaches. Much of the earlier work was emphasized by security issues but with the end of the Cold War attention turned toward preventive approaches. This paper argues that the incentive for loss prevention leads to some form of cooperative regional integration. Inclusion of uncertainty positively contributes to the overall customs union literature. The optimal level of integration, political or economic, is found and then using simple comparative statics, the effects of some changes in the underlying parameters of the economy on the optimal level of integration are examined. Multilateralism and regionalism are concluded to be complements.
Keywords: F02; F15; 330; Self-protection; Uncertainty; Economic Integration; Multilateralism; Regionalism; Handelsregionalismus; Wirtschaftsintegration; Handelsabkommen; Protektionismus; Kosten-Nutzen-Analyse; T